2008
DOI: 10.1002/adma.200702566
|View full text |Cite
|
Sign up to set email alerts
|

Actuating Single Wall Carbon Nanotube–Polymer Composites: Intrinsic Unimorphs

Abstract: A novel actuating single wall carbon nanotube (SWNT)/polymer composite is reported. It exhibits a large strain (2.6%) at a low driving voltage (<1 MV m−1) while possessing excellent mechanical and thermal properties. The strain energy density is at least an order of magnitude greater than any state‐of‐the‐art polymeric materials reported. The actuating characteristic mainly originates from the electrostrictive contribution, presumably due to interfacial polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 22 publications
(22 reference statements)
5
65
0
Order By: Relevance
“…Once percolation is achieved, however, we find enormous increases in the low frequency permittivities, as expected for materials exhibiting conductive behavior. Interfacial polarization at the surface of the SWCNTs is responsible for this increase at low frequencies and a similar observation has been reported elsewhere 21,22 . An order of magnitude increase in the permittivity is observed between the pure polymer (2.95) and the 0.75 wt% sample (35.48) at 1 kHz.…”
supporting
confidence: 69%
“…Once percolation is achieved, however, we find enormous increases in the low frequency permittivities, as expected for materials exhibiting conductive behavior. Interfacial polarization at the surface of the SWCNTs is responsible for this increase at low frequencies and a similar observation has been reported elsewhere 21,22 . An order of magnitude increase in the permittivity is observed between the pure polymer (2.95) and the 0.75 wt% sample (35.48) at 1 kHz.…”
supporting
confidence: 69%
“…Carbon nanotubes have aroused increasing interest due to their remarkable tensile strength, high mechanical strength, flexibility brilliant electrical and physicochemical properties and other unique structural, mechanical characteristics [7][8][9][10]_ENREF_6_ENREF_8. Attempts have been made to create advanced engineering materials with new or better properties through the incorporation of CNT in the selected matrices such as polymers, metals and ceramics [11].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, SWCNTs are promising as filler materials in polymer-based composites due to their ability to enhance the performance of matrices. It has been demonstrated that incorporation of SWCNTs into polymers enhances mechanical [5], electrical [6], and thermal properties [7], and therefore, SWCNT/polymer composites have opened up new device applications such as actuators [8,9], sensors [10], and photonic devices [11].…”
Section: Introductionmentioning
confidence: 99%